E-Learning Enhanced by Web 2 Technologies and Blackboard Services - Philip, Mathew (Indian Journal of Marketing, 2010)
In today’s globally competitive environment, computing technologies allow new opportunities for teachers and learners to be more connected. The Web is becoming the largest data repository in the world and presents a key driving force for a large spectrum of information technology (IT). Tremendous modern tools which support the E-learning process and ease the creation of instruction materials using updated technologies will help for the implementation work in the ubiquitous computing learning society. On the other hand, Web Intelligence has been recognized as a new direction for scientific research and development to explore the fundamental roles and practical impacts of Artificial Intelligence and advanced Information Technology on the next generation of Web services. It is one of the most important as well as promising IT research fields in the era of web technology. How to benefit from intelligent Web-based information systems through the mining of diverse Web data resources is being used in many emerging areas of Web knowledge. To develop effective Web applications and services, it is critical to discover useful knowledge through analyzing large amounts of contents, hidden content structures, or usage patterns of Web data resources. To achieve such a goal, a variety of techniques in diverse areas are needed to integrate properly: besides natural language processing, information extraction, information retrieval, information filtering, knowledge representation, knowledge management, machine learning, databases, data mining, Web mining, text mining, agent, human-computer interaction, and semantic Web etc.